2019
DOI: 10.3389/fpsyg.2019.01128
|View full text |Cite
|
Sign up to set email alerts
|

Socially Communicative Eye Contact and Gender Affect Memory

Abstract: Because of their value as a socially communicative cue, researchers have strived to understand how the gaze of other people influences a variety of cognitive processes. Recent work in social attention suggests that the use of images of people in laboratory studies, as a substitute for real people, may not effectively test socially communicative aspects of eye gaze. As attention affects many other cognitive processes, it is likely that social attention between real individuals could also affect other cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 151 publications
(272 reference statements)
1
8
0
Order By: Relevance
“…Nevertheless, such effects might be weakened or not exist when people are not interested in such information. Our empirical findings seem congruent with those reported by Lanthier et al (2019), who indicated that men and women respond to a direct gaze differently, i.e. eye contact improves word recognition only among women.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, such effects might be weakened or not exist when people are not interested in such information. Our empirical findings seem congruent with those reported by Lanthier et al (2019), who indicated that men and women respond to a direct gaze differently, i.e. eye contact improves word recognition only among women.…”
Section: Discussionsupporting
confidence: 91%
“…Second, prior studies typically concentrate on the isolated impact of a direct gaze (Falck-Ytter et al , 2015; Lopis and Conty, 2019); few studies investigated the moderating effect of the viewer's gender (Lanthier et al , 2019). Studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, if a speaker's direct gaze draws the addressee's attention to the speaker's eyes, as shown by previous research (e.g., Böckler et al, 2014, who Alternatively, however, one could predict that a speaker's direct, ostensive gaze leads to a general increase in the addressee's attention because she feels personally addressed and is eager to understand the speaker's message (cf. Csibra & Gergely, 2009;Lanthier et al, 2019Lanthier et al, , 2021. When the speaker speaks with closed eyes, the addressee might not consider herself the intended recipient of the message and thus not pay as much attention.…”
Section: Predictions For Eyesmentioning
confidence: 99%